HUBUNGAN ANTARA TINGKAT KECEMASAN DIGITAL DENGAN PENDEKATAN PEMBELAJARAN MENDALAM (DEEP LEARNING) PADA MATERI PROSES KOMPUTASI SISWA KELAS X TKL DI SMK NEGERI 5 KUPANG - Mamida Yosefa Boko, Heddy; J. Taku Neno, Katrin; Enstein, Jhon (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the relationship between digital anxiety and the deep learning approach to computational process material among 10th-grade TKL students at SMK Negeri 5 Kupang. This research utilizes a quantitative correlational method. The study was conducted at SMK Negeri 5 Kupang from February to July 2026. The research population consisted of all 67 students from class X TKL, while the sample was selected using total sampling from class X TKL 2, comprising 33 students. Data collection was carried out through the simultaneous distribution of digital anxiety scale questionnaires (adapted from DASS), interview guidelines, and documentation sheet verification. Data analysis was performed using Pearson Product-Moment correlation statistical analysis via SPSS 31 after fulfilling the prerequisite normality tests (Shapiro-Wilk) and linearity tests. The results demonstrated a significant negative or inverse correlation between digital anxiety (Variable X) and the deep learning approach (Variable Y) with a correlation coefficient (rxy) of -0.347 and a significance value of 0.048 (Sig. < 0.05). This indicates that higher digital anxiety in students when operating computers corresponds to lower deep learning levels. Qualitative field findings revealed that students' digital anxiety is triggered by fear of clicking wrong buttons, error messages, and English-heavy interfaces, causing them to choose shortcuts like copying tasks. Therefore, creating a calm, quiet laboratory environment and implementing step-by-step humanistic teaching methods are essential strategies to reduce digital anxiety and foster an optimal deep learning culture in computing subjects.